Human immunodeficiency virus (HIV) nef-specific cytotoxic T lymphocytes in noninfected heterosexual contact of HIV-infected patients. - Langlade-Demoyen, P (1994)
We report on the detection of HIV-specific cytotoxic T lymphocytes (CTL) among 23 regular partners of HIV-infected individuals. 15 of the 46 individuals enrolled in the study were positive for HLA-A2.1 typing. Among the 23 contacts studied, 7 were seropositive and 16 were seronegative on repeated tests. None of the 16 seronegative contacts were positive for p24 antigenemia nor were they positive by the lymphocytes coculture assay, although, in two instances HIV-1 DNA could be detected by PCR (in one case using a gag SK 38/39 primer, and in the other using a primer for the pol P3/P4 primer). These two individuals remained seronegative for 18 and 36 mo, respectively. HIV-specific cytotoxicity was performed in the 15 HLA-A2.1 subjects (7 indexes, 2 seropositive contacts, and 6 seronegative contacts) and in 4 HLA-matched HIV negative donors. CTL specific for env, gag, or nef proteins could not be detected in unstimulated bulk cultures of peripheral blood lymphocytes in any of the six seronegative contacts. However, using a limiting dilution assay we found an usually high frequency of HIV nef-specific CTL precursors (CTLp) for HIV env and gag was very similar to that observed in seronegative HLA-matched healthy donors. Because no presence of HIV could be demonstrated in these individuals, these findings argue against the possibility of a silent HIV infection and suggest that a CTL response against nef may be involved in a rapid and effective clearance of the virus after sexual exposure.